Latino Catholicism Transformation in America's Largest Church. - Matovina, Timothy (Princeton : Princeton University Press, 2011)
Most histories of Catholicism in the United States focus on the experience of Euro-American Catholics, whose views on such concerns as church reform, social issues, and sexual ethics have dominated public debates. Latino Catholicism provides a comprehensive overview of the Latino Catholic experience in America from the sixteenth century to today, and offers the most in-depth examination to date of the important ways the U.S. Catholic Church, its evolving Latino majority, and American culture are mutually transforming one another. Timothy Matovina assesses how Latinos' attempts to celebrate the.
Cover; Contents; Preface; Abbreviations; 1 Remapping American Catholicism; 2 Integration; 3 Hispanic Ministry; 4 Parishes and Apostolic Movements; 5 Leadership; 6 Worship and Devotion; 7 Public Catholicism; 8 Passing on the Faith; Epilogue: Transformation in America's Largest Church; Notes; Bibliography; Index; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; Q; R; S; T; U; V; W; Y; Z
Description based upon print version of record.
Keywords: Catholic Church -- United States; Hispanic American Catholics -- Religious life; Religion; Catholic Church -- United States; Hispanic American Catholics -- Religious life; RELIGION / Christianity / Catholic; Electronic books